Low-carbon optimal operation of the integrated energy system considering integrated demand response - Ji, Xiu; Li, Meng; Li, Meiyue; Han, Huanhuan (Frontiers in Energy Research, 2023)
In order to further explore the impact of the integrated energy system (IES) demand-side regulation potential on carbon emission reduction, a demand response considering the low-carbon optimized operation strategy of the electricity-gas-heat integrated energy system is proposed. First, according to the load response characteristics, the demand response is divided into price-based demand response and alternative demand response, and a price-based demand response model based on the energy price elasticity matrix and an alternative demand response model considering mutual conversion are established for different energy sources. Secondly, according to the actual carbon emissions of system equipment, introduce a green certificate-ladder carbon trading mechanism; finally, the goal is to minimize the sum of energy procurement costs, green certificate-ladder carbon trading costs, operation and maintenance costs and new energy penalty costs. function to establish a low-carbon optimized operation model of the integrated energy system. Through numerical simulation verification, the model can achieve low-carbon economic operation of the integrated energy system.